Pengembangan Rubrik Penilaian Autentik Berbasis Metode Pembelajaran Abad 21 untuk Penilaian Semester II Kelas 11 SMA - Saputra, Pande Kadek Dika; Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu (Universitas Pendidikan Ganesha, 2023)
The purpose of this study is to create an authentic assessment rubric using Problem-Based Learning (PBL) based learning, project-based learning (PjBl), and discovery learning, three 21st-century learning strategies. This study employed the Richey and Klein (2007) design and development (DnD) approach, which has four stages: analysis, design, development, and evaluation, or ADDE. The participants in this study were a senior high school English instructor and 11th graders. The data was gathered using a variety of tools, including surveys, interviews, and document analyses, and was then examined using a mixed technique. Instructions for instructors and students as well as the proper assessment methods were included in the created rubric. The developed rubric then produced an appropriate and unique product that is in line with the syntax of each teaching method. It has been specifically adapted for the learning objectives, topics, themes, teaching strategies, from the expert's examination, it can be concluded that the product developed can be categorized as a superior rubric that is suitable for learning English